Makna Hari Raya Nyepi Sebagai Peningkatan Spiritual - Ni Wayan Gateri (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2021)
The implementation of Nyepi as a milestone for Hindus to be aware and self-aware, to remember and reflect on all the behaviors that have been done during the year. Nyepi day is a very good day to uphold your true self. During Nyepi day, we as human beings keep in mind the essence of truth, because truth is what is lasting, others are not eternal. On Nyepi day, it is a real effort to be able to control oneself, hold back, not go into indignation, not be extravagant, and not behave arrogantly towards anyone. Likewise, the behavior of gambling and the like can be controlled, because it is a very big sin for mankind. By interpreting the essence and meaning of the Nyepi celebration with all its series of ceremonies, it is hoped that a noble heart and soul will be full of holiness in the next life. Only the truth that lasts. Pursue the truth through the implementation of Catur Brata Penyepian, in order to realize happiness.